Subversion of neo-imperialist hegemony: A postcolonial study of Red Birds by Mohammed Hanif - Tilwani, Shouket Ahmad; Hassan, Ahdi (Universitas Syiah Kuala, 2024)
Although the erstwhile colonies in the Third World are free from the colonial occupation, the imperialist hegemony continues, to be resisted in the societies. For, such enterprise has provided the pretext for the concepts of Self and Other followed by occupation, a reign of violence and terror loosened upon the natives. This paper aims to study Red Birds (2018) a novel by Mohammed Hanif to highlight the plight of the Other with their aggressive vitality and fervor of resistance to counter the imperialist agenda-hegemony. As qualitative research, it employs the postcolonial method, while seeking theoretical insights from the arguments of Orientalism by Edward Said, and the theory of hegemony by Antonio Gramsci to be interpretive in nature to analyze the text. It explores how the text, gleaned selectively from the novel offered, like Orientalism a fabric of textual analyses that is highly critical of the Eurocentric notions and hegemony of the Western world. It underlines the ways and practices sketched by the novel through the troubling encounter of the characters from the East to the West to offer a subversive narrative to the failure of the efforts and narratives of the West. For better analyses of the text to underline the American neo-imperialism and the native dreams of subversion, it takes to the tone of Gramscian precepts to conclude that the powerful subjugates through hegemonythe geo-political method used to gain indirect imperial dominance which is maintained mainly through ideology instead of using means like economic force, or coercive strategies.